Annual cycle variations in the gut microbiota of migratory black-necked cranes - Zhang, Yujia; Ma, Ruifeng; Suolangduoerji,; Ma, Shujuan; Nuertai, Akebota; He, Ke; Liu, Hongyi; Zhu, Ying (Frontiers in Microbiology, 2025)
IntroductionMigratory birds exhibit unique annual cycles that complicate their gut microbiota. However, the annual dynamics of gut microbiota in migratory birds remain unclear, hindering our understanding of their environmental adaptation.MethodsHere, we collected fecal samples from black-necked cranes (Grus nigricollis) across four seasons at their breeding grounds and used wintering ground data from databases to characterize their gut microbial compositions throughout the year.Results and discussionThe results showed that the gut microbiota was clustered by season (Bray-Curtis: R2 = 0.348, p < 0.001; UniFrac: R2 = 0.352, p < 0.001). And the summer samples exhibited higher alpha (Simpson and Shannon), beta diversity (Bray-Curtis and UniFrac) and more diverse functions in gut microbiota compared to other seasons. Furthermore, in summer, the gut microbiota exhibited several balanced relative abundances at the family level, whereas Lactobacillaceae family dominated during the other seasons. Thirty-six ASVs were identified by random forest analysis to distinguish samples from distinct seasons. Despite having greater diversity, the summer gut microbiota had a simpler network structure than the other seasons (fewer edges and nodes). The dispersal limitation during random processes also significantly influenced gut microbial community assembly. Overall, the gut microbiota of the black-necked crane undergoes dynamic adjustments to adapt to seasonal environmental changes, which may be associated with the variations in diet across seasons. These results enhance our understanding of the gut microbiota of wild migratory birds and support further research on black-necked cranes.